IMPLEMENTASI IC TIMER 555 PADA SISTEM ELEKTRONIKA DASAR UNTUK APLIKASI KENDALI, INDIKATOR, DAN KEAMANAN - Bonardo, Doli; Harahap, Basyaruddin Ismail; Suharlan, Didy; Harahap, Rahmat Kholis (Politeknik Negeri Indramayu, 2025)
Within the context of energy-efficient automation, simple electronic control systems remain an essential research area for practical yet low-cost solutions. This study aims to evaluate the functional performance of two circuit prototypes based on the IC Timer 555 a Laser-LDR Security Alarm and a Blinking Turn-Signal Light to address the need for reliable automation in energy engineering applications. The methodology follows a structured three-step approach: (1) circuit simulation using tools such as Multisim or Proteus, (2) physical realization via PCB design and assembly, and (3) functional testing to verify performance metrics of each prototype. Results demonstrate that the security alarm effectively detects laser beam interruption via the LDR in a monostable (latch) configuration, while the turn-signal circuit reliably generates periodic LED blinking using the astable mode. Together, these prototypical systems illustrate how simple timing control circuits using IC 555 can deliver versatile, cost-effective automation suitable for practical applications in energy engineering.